(untitled) (Global Journal of Human-Social Science, 2022)
Evidence in studies from different fields point to the harmfulness of being bullied on indicators of success in an individual s life Aiming to measure and understand the impact of this inherently social event this paper investigates how the friendships of lower secondary education students in the city of Recife influence their likelihood of being victims of such a phenomenon and its effect on the academic performance of these students The two-stage least squares method is applied to an IV-SLX model using indirect friendship ties as an instrument and significant results are found at 95 confidence increasing the chances of being victimized by bullying by 10 on average reduces the Portuguese language score by 2 33 and the math score by 2 75